Etika Digital dan Teknologi Kunci Kewirausahaan dalam Industri 4.0 - Sriyeni, Yesi; Effendi, Hendra; Veronica, Maria; Everhard, Jan (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The Fourth Industrial Revolution has transformed the labor market structure through digitalization, automation, and the integration of technologies such as AI, IoT, and big data. One of the most evident impacts is the emergence of the gig economy—a platform-based work model that offers high flexibility but is often accompanied by income uncertainty, limited job security, and minimal legal protection. These conditions give rise to serious ethical dilemmas, particularly regarding the power imbalance between workers and platform companies. This study aims to analyze the application of digital ethics principles in entrepreneurial practices within the gig economy and to identify the emerging ethical challenges. The method used is a literature review focusing on digital entrepreneurship, gig economy characteristics, and the principles of business ethics and algorithmic ethics. The results indicate that fairness, honesty, responsibility, and transparency are fundamental to ethical entrepreneurship in the digital context. Algorithmic transparency, fair compensation, human-centered management approaches, and strong regulatory interventions are essential to ensure worker well-being and protection. These findings highlight the crucial role of digital ethics as a balancing force in building an inclusive and sustainable platform-based work ecosystem. Keywords— Digital Ethics, Industry 4.0, Gig Economy, Enterpreneurial Ethics